تحقيق مجمل ما ذكر من القول في صحيح البخاري على سبيل المذاكرة قسم المعاملات – أنموذجا - شيباني, بشيرة (University of Eloued جامعة الوادي, 2017)
تناولت في هذا الموضوع مسلكا مهما من مسالك صيغ الأداء والتحمل عند الإمام البخاري والمتمثلة في صيغة المذاكرة، وقد ابنت في إشكالية البحث الألفاظ التي يستعملها البخاري في مجالس التحديث ومقصده منها، وكان الدافع الأساسي لدراسة هذا الموضوع معرفة مقصد البخاري من قوله "قال لنا " و"قال لي "، وقد اشتمل البحث على مقدمة ومبحثين نظريين، فخصصت المبحث الأول التعريف بالإمام البخاري وكتابه الجامع، والمبحث الثاني التعريف بالمذاكرة أغراضها وأنواعها وأداء الحديث فيها، وقد كان تركيزي على الجانب التطبيقي والذي له ثلاث مباحث، مبحث خصصته إلى دراسة الأحاديث الواردة في أبواب البيوع ولأنكحه والفتن والألبسة، والمبحث الرابع تحدثت فيه على الأحاديث الواردة في أبواب الواردة في أبواب أخري متفرقة محاولة بذلك في الجانب التطبيقي بيان درجتها ورأي المحدثون في صيغة ورودها. وأخيرا جعلت لهذا الدراسة خاتمة ذكرت فيها أهم النتائج التي توصلت إليها من خلال هذا البحث، وختمت عملي بالفهارس العلمية. In this subject I treats an importomte way among cellies of per fermance and laiman And bukhari it is of the revsion In the introduction I demonstrate the vocalles used by bukhari at the level of the reminders of hadithe and also the lrut dercere these voceles To this etusle I want to demonstrate limten this imam to say "il ema dude" and "he told us" this research is Realized in an intrusion and two chapters theoupnes In the first chart of the lrograph of this imaet live "EL djamea" "lemglobant", then stinked in the dual chapter I have pobe to repeat the hadithe to the brain of this "revision", I focus on the cotipue or cons conscere Three chapies in the first is devoted to the hadiths, which deals with sales, conflicts, bullfights and shrimps, the chapter is devoted to speaking of the "djhade" and condescending them in the copse. In trying to demonstrate in the partitions of the hadiths (rightness, falsehood), and in the presence of sovereigns of hahiths containing the manner in which they were finally resurrected, I had a Or I have cited the results obtained at the end of this research, mentioning the tangles of material at the end of this research
مذكرة ماستر تخصص علوم الحديث
Keywords: مجالس التحديث، المذاكرة، الإمام البخاري; Councils of modernization, study, Imam Boukhari